(untitled) (Al-Academy, 2018)
The Arab Islamic art was best known as pure abstraction or realism distorted from what is natural. The two styles, or one of them, was the most prominent in the Islamic arts, such as decoration, photography and architecture. The analogy that was prevalent in the non-Islamic world did not have a presence equivalent the aforementioned styles despite the great openness to the cultures of different countries, which characterized that stage, which resulted from the Islamic conquests, the conversion of many people to the Islamic faith, and their migration to the Islamic cities at the time, bringing with them their arts and methods of formulation. This makes us question the influential references that invite the Arab Muslim artist to follow the abstract method and stick to it. That was the problem of the research included in the methodological framework, which also included the research importance, purpose and limits and specifying its terms. The theoretical framework consisted of two sections: the first (the pressure of the aesthetic thought), and the second (the pressure of the religious reference). The researcher came up with a number of indicators. The research procedures for the analysis of the sample, depended on the indicators of the theoretical framework, which represented the analysis tool through which the results and conclusions of the research have been reached at and the most important of which: 1- The Islamic religious reference was pressing towards the method of abstraction as it is a natural result of the Arab transformation from the pagan creed to the spiritual doctrine of Islam; that the expression through art about what is spiritual - even for non-Muslims, such as the African negro - takes abstraction quality, which means that abstraction of the Arab-Islamic art is a necessity; to express the invisible and the infinite, even if there is no disobedience or prohibition of the method of imitation. 2- The aesthetic thought is an influential reference reflected by the artist’s output. Its product was based on the aesthetic values of Islam: moderation, harmony, proportionality and organization in an attempt to follow the divine perfection which is the secret of beauty.